Synthesis and properties of (±)-trans-2-dialkylaminoethylaminocyclohexanols. - Vu Hon Shon; N. Yu. Borisova; E. Yu. Afanasieva; G. A. Fomicheva; T. P. Kolobova; E. Ya. Borisova (Тонкие химические технологии)
This article is devoted method of synthesis and study of the properties of (±)-trans-2- dialkylaminoethylaminocyclohexahols. It was found that the studied compounds are not toxic and have expressed antiarrhythmic properties. It was found that the explored compounds are low-toxicity substances having pronounced antiarrhythmic properties.